Unusual Electrical Presentation of Ebstein’s Anomaly – A Case Report - Qumruzzaman, KH; Hoque, Harisul; Shahriar, Md Saqif; Ahmed, Khurshed; Saha, Debbroto; Newaz, Syed Ashraf; Fatema, Nilufar (University Heart Journal, 2025)
Ebstein’s anomaly is a rare congenital heart disease. A 24 yrs male presented with shortness of breath for 6 weeks and palpitation for same duration. On examination, he found to have Pan-systolic murmur of 3/6 grading present over the left lower parasternal area with no radiation and prominent on inspiration. ECG shows wide QRS complex, Left axis deviation suggestive of LBBB. Chest X-Ray P/A view shows Cardiomegaly. Echocardiography shows septal leaflet of Tricuspid valve 37 mm apically displaced with large RA due to atrialization of RV, small RV and elongated anterior tricuspid leaflet with sail like appearance and partially restricted with RV free wall, moderate TR. So our case is Ebstein’s Anomaly (Type C) with LBBB which is a rare variety as the common presentations are typical RBBB with the presence of qR pattern in V1 also suggests an enlarged atrialised RV. University Heart Journal 2024; 20(1): 44-46